1988
DOI: 10.1002/j.1460-2075.1988.tb03038.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody engineering for the analysis of affinity maturation of an anti-hapten response.

Abstract: The influence of structural variation, previously observed in a panel of V186.2 VH/V lambda 1‐expressing anti‐NP antibodies from the secondary response, on the affinity of these antibodies was examined by site‐specific mutagenesis and recombinant antibody construction. A tryptophan––leucine exchange at position 33 in the VH segment of all but one of the high‐affinity antibodies is the most frequently observed somatic mutation and by itself leads to a 10‐fold higher affinity; all other somatic exchanges are irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(166 citation statements)
references
References 34 publications
4
161
1
Order By: Relevance
“…However, mutations in the V L regions were not apparently increased in the comparison of the anti-NP mAbs from Ganp Tg and C57BL/6 mice. The generation of high-affinity BCR without the exchange at position 33 is a rare event, which suggested that the combination of particular D-J H sequences and/or many SHMs do not result in high affinity (18). A recent report only showed the case of mutation, Y99G in V H 186.2, which generated similar high-affinity mAb against NP-hapten comparable to W33L (10).…”
Section: The Usage and Mutation Of V Region Genes In The Anti-np Hybrmentioning
confidence: 99%
“…However, mutations in the V L regions were not apparently increased in the comparison of the anti-NP mAbs from Ganp Tg and C57BL/6 mice. The generation of high-affinity BCR without the exchange at position 33 is a rare event, which suggested that the combination of particular D-J H sequences and/or many SHMs do not result in high affinity (18). A recent report only showed the case of mutation, Y99G in V H 186.2, which generated similar high-affinity mAb against NP-hapten comparable to W33L (10).…”
Section: The Usage and Mutation Of V Region Genes In The Anti-np Hybrmentioning
confidence: 99%
“…39 It is possible that a minimum number of amino acid substitutions in CDRs might ultimately confer a great increase in affinity for antigen and favor selection; this has been convincingly shown in hybridomas producing monoclonal antibodies, where a single amino acid replacement in CDRs by site-directed mutagenesis may cause a 10-fold rise in affinity. 40 Therefore, it is not impossible to have a relatively modest R:S mutation ratio in CDRs and yet attain optimal conditions for high-affinity antigen binding. Moreover, a statistically significant low R:S ratio in FWRs in such situations might in itself constitute a surrogate measure for non-random distribution of mutations suggestive of selection by antigen.…”
Section: Somatic Hypermutation Of MM V H Genesmentioning
confidence: 99%
“…Third, the DJ join that contains the 3-bp deletion in the tDL is otherwise identical to the FL consensus sequence for this region. Fourth, somatic mutation in Ig genes can include deletion of an entire codon (46,47) . The finding that 4 of the 28 mutations observed among the eight FL clones occurred in this 15-bp stretch where only one would have been expected if the mutations were distributed evenly suggests that the DJ join is a target for active mutation .…”
mentioning
confidence: 99%